Analisis Implementasi Pelayanan Administrasi Terpadu Kecamatan (PATEN) Terhadap Kualitas Pelayanan Publik Di Kecamatan Bojongsoang - Muhammad Gilang Pratama; Etti Ernita Sembiring (Indonesian Accounting Research Journal, 2020)
This study aims to describe and find out the quality of public services by implementing PATEN in Bojongsoang District. This research uses descriptive qualitative method with 5 determinants according to Parasuraman (1988) to measure the quality of service. The results of this study include PATEN that have been implemented quite well in Bojongsoang District, but there are some things that are not yet optimal. The quality of public services in Bojongsoang District is quite good, people who gets service is satisfied with the services. obstacles faced by Bojongsoang District in implementing PATEN is network constraints which sometimes have problems as well as maintenance causing Bojongsoang District to not be able to provide one-day service to the community, broken queuing machines have not been repaired even though they have proposed repairs. and the incomplete service procedure flowchart for each service resulted in the discovery of people carrying incomplete document requirements.